Human papillomavirus (HPV) persistence and HPV 31 predict the risk of recurrence in high-grade vaginal intraepithelial neoplasia. (March 2017) - Bogani, Giorgio; Martinelli, Fabio; Ditto, Antonino; Taverna, Francesca; Lombardo, Claudia; Signorelli, Mauro; Chiappa, Valentina; Leone Roberti Maggiore, Umberto; Fontanella, Caterina; Sabatucci, Ilaria; Borghi, Chiara; Recalcati, Dario; et al.
Abstract: Objective: High-grade vaginal intraepithelial neoplasia (vaginal HSIL) represents an uncommon entity. Here, we sought to identify predictors for recurrence and risk factor for developing genital cancers after primary treatment for vaginal HSIL. Methods: Data of consecutive 5104 women who had human papillomavirus (HPV) DNA test were searched for identify women with histological confirmed vaginal HSIL. Disease-free interval and the risk of developing HPV-related gynecological cancers were assessed using Kaplan-Meier and Cox proportional hazard models. Results: Overall, 77 patients were included. After a mean (SD) follow-up of 69.3 (33.0) months, 11 (14%) and 4 (5%) patients experienced vaginal HSIL recurrence and the occurrence of HPV-related gynecological cancers, respectively. Via multivariate analysis factors predicting for vaginal HSIL recurrence were infection from HPV31 at diagnosis (HR: 5.0 (95%CI:1.17, 21.3); p = 0.03) and persistence of HPV infection after treatment (HR: 7.0 (95%CI:1.54, 31.6); p = 0.01). Additionally, patients who had LASER ablation experienced a trend toward a lower risk of recurrence in comparison to medical treatment (HR: 0.20 (95%CI:0.03, 1.09); p = 0.06). Considering the occurrence of HPV-related gynecological cancers, we observed that no factors independently correlated with this risk; while, a trend towards higher risk was observed for women with HIV infection (HR:16.4 (95%CI:0.90, 300.1); p = 0.06) and persistence of HPV infection (HR: 13.3 (95%CI:0.76, 230.2); p = 0.07). Conclusions: Patients affected by vaginal HSIL experienced a relatively high risk of recurrence. Persistence of HPV after treatment and pretreatment HPV-31 infection predicts for high-grade vaginal intraepithelial neoplasia recurrence. Further investigations are warranted in order to corroborate our data.